2020
DOI: 10.5606/tgkdc.dergisi.2020.18983
|View full text |Cite
|
Sign up to set email alerts
|

Application of autologous blood patch in patients with non-expanded lungs and persistent air leak

Abstract: Background: This study aims to evaluate the effectiveness of pleurodesis procedure by ensuring the expansion of the lung and occluding lung parenchyma leaks with an autologous blood patch. Methods: A total of 24 patients (17 males, 7 females; mean age 59.9±12.2 years; range, 30 to 86 years) who underwent autologous blood patch pleurodesis in our clinic between November 2015 and November 2019 were retrospectively analyzed. The patients were not eligible to undergo chemical pleurodesis due to a non-expandable lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The main side effects reported are fever and empyema. Of note, the procedure is usually painless, and no sedatives or analgesics are needed [10]. In their research, Oliveira et al found other studies with an 84-100% success rate for autologous blood patches for persistent air leaks, including their own success rate of 85% [4].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The main side effects reported are fever and empyema. Of note, the procedure is usually painless, and no sedatives or analgesics are needed [10]. In their research, Oliveira et al found other studies with an 84-100% success rate for autologous blood patches for persistent air leaks, including their own success rate of 85% [4].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment and pleurodesis are commonly performed to overcome a pneumothorax [1,10]. In chemical pleurodesis, agents such as talc powder, tetracycline derivatives, and bleomycin are used to eliminate the space between the parietal and visceral pleura and, thus, seal the air leak [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations